A2BC-type porphyrin SAM on gold surface for bacteria detection applications: synthesis and surface functionalization - Neumann, Laurie; Könemund, Lea; Rohnacher, Valentina; Pucci, Annemarie; Johannes, Hans-Hermann; Kowalsky, Wolfgang (Materials, 2021)
Currently used elaborate technologies for the detection of bacteria can be improved in regard to their time consumption, labor intensity, accuracy and reproducibility. Well-known electrical measurement methods might connect highly sensitive sensing systems with biological requirements. The development of modified sensor surfaces with self-assembled monolayers (SAMs) from functionalized porphyrin for bacteria trapping can lead to a highly sensitive sensor for bacteria detection. Different A2BC-type porphyrin structures were synthesized and examined regarding their optical behavior. We achieved the synthesis of a porphyrin for SAM formation on a gold surface as electrode material. Two possible bio linkers were attached on the opposite meso-position of the porphyrin, which allows the porphyrin to react as a linker on the surface for bacteria trapping. Different porphyrin structures were attached to a gold surface, the SAM formation and the respective coverage was investigated.